2021
DOI: 10.2147/opth.s336727
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Transepithelial Photorefractive Keratectomy with WaveLight EX500 Platform for Adolescents and Adults with Low to Moderate Myopia: A 12-Month Comparative Evaluation

Abstract: Purpose: To compare the visual and refractive results obtained after two-step TransPRK using an EX500 excimer laser for low to moderate myopic correction in adolescents and adults. Patients and Methods: Retrospectively, 91 eyes of 52 patients were categorized into four groups based on age and level of myopia. The demographics, data of efficacy, safety, predictability, stability, and post-operative complications were evaluated at 1, 3, 6, and 12 months post-operatively. Results: At 1-month, adolescents with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…On the one hand, the t PRK method has been proven many times as a safe and effective way to treat myopia [ 7 ]. On the other hand, the PTK−PRK procedure seems to show stable results, as demonstrated previously by two groups [ 8 , 9 ] with the EX500 laser (Alcon Laboratories). Also, older publications indicate that the PTK−PRK combination is an effective treatment [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…On the one hand, the t PRK method has been proven many times as a safe and effective way to treat myopia [ 7 ]. On the other hand, the PTK−PRK procedure seems to show stable results, as demonstrated previously by two groups [ 8 , 9 ] with the EX500 laser (Alcon Laboratories). Also, older publications indicate that the PTK−PRK combination is an effective treatment [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 78%
“…This is the first study comparing the t PRK technique using the Amaris750 with PTK−PRK performed with MEL90. Tangmonkongvoragul et al demonstrated good refractive results of the PTK−PRK method for treating mild myopia with the EX500 excimer laser [ 8 ]. A recently published study also confirmed the efficacy of PTK−PRK surgery compared to t PRK treatment [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transepithelial photorefractive keratectomy (PRK) is safe and effective for treating low-to-moderate myopia, and compared with alcohol-assisted PRK, it is associated with less postoperative pain, faster reepithelialization and visual recovery, less tissue removal, less haze, and shorter surgical times. [ 20 , 21 ] Another advantage of transepithelial PTK in treating surface irregularities is that the epithelium works as a natural masking agent which enhances the outcomes of surface smoothing following PTK. [ 22 ] In our study, around 74% of eyes ( n = 31) underwent transepithelial PTK, all 31 eyes had timely healing of epithelial defects with no delay.…”
Section: Discussionmentioning
confidence: 99%